Combined precompetitive mental conditioning model customized for pandemic-related limitations - Banayan, A. A.; Lashkul, A. K. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to develop a new combined precompetitive psychological training model customizable for the pandemic-related limitations.